2009 IEEE International Symposium on Broadband Multimedia Systems and Broadcasting 2009
DOI: 10.1109/isbmsb.2009.5133781
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temporal pooling method on the objective video quality evaluation

Abstract: Objective video quality evaluation incorporates spatial and temporal degradation effects to calculate quality grade for each video frame alone, as well as the overall quality grade for the whole sequence. Distortion visibility depends not only on the level of degradation but also on video content and viewer's preferences. Temporal pooling is a method that collapses series of frame quality scores to one quality score for whole video sequence and it should be aware of an influence of the video quality variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…Simple temporal average pooling is a widely used scheme to augment both FR [11][12][13] and NR VQA models [5,7,9]. Other kinds of pooling that are used include harmonic mean [14], Minkowski mean [15,16], percentile pooling [17,18], and adaptively weighted sums [19]. More sophisticated pooling strategies have considered memory effects, such as primacy, recency [15,16,20], and hysteresis [6,10,21,22].…”
Section: ⋆ Equal Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple temporal average pooling is a widely used scheme to augment both FR [11][12][13] and NR VQA models [5,7,9]. Other kinds of pooling that are used include harmonic mean [14], Minkowski mean [15,16], percentile pooling [17,18], and adaptively weighted sums [19]. More sophisticated pooling strategies have considered memory effects, such as primacy, recency [15,16,20], and hysteresis [6,10,21,22].…”
Section: ⋆ Equal Contributionmentioning
confidence: 99%
“…Other kinds of pooling that are used include harmonic mean [14], Minkowski mean [15,16], percentile pooling [17,18], and adaptively weighted sums [19]. More sophisticated pooling strategies have considered memory effects, such as primacy, recency [15,16,20], and hysteresis [6,10,21,22]. The general applicability of these pooling models, however, has not so far been deeply validated in the general context of NR VQA models for real-world UGC videos, though a few more directed studies have been conducted [15,16].…”
Section: ⋆ Equal Contributionmentioning
confidence: 99%
“…Rimac-Drlje et al [270] compared different pooling methods for different image quality metrics and suggest Minkowski summation over all frames, but results by You et al [372,374] indicate that Minkowski summation does not provide any advantage compared to simple averaging.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review found several di erent temporal pooling methods, which are investigated in this study. The most intuitive approaches described in [244] are mean pooling (Mean, 1 T • T t=1 OM (t)) and last frames mean pooling (Mean-LastFrames, 1 F • T t=T −F OM (t)). These methods simply average the objective metrics over all frames, or the F most recent frames, respectively.…”
Section: Temporal Poolingmentioning
confidence: 99%
“…1/p ) by tuning the parameter p. The additional parameter τ in ExpMinkowski controls the exponential weighting, and thus, the recency e ect. Moreover, [244] OM (t + i)]) also accounts for the poorest quality section. A related method, which was not described in [244], computes the mean of the p percent of overall frames with lowest quality (Percentile).…”
Section: Temporal Poolingmentioning
confidence: 99%